A Balance Sheet Perspective on Financial Success: Why Starting Early Matters1. Issue 1 (18th January 2015) - BOSHARA, RAY; EMMONS, WILLIAM R.
<x xml:space="preserve">Abstract</x> This paper offers four ideas. First, a balance sheet perspective on financial success is constructive, and that a meaningful measure of the success of financial capability efforts is the health of one's balance sheet. Second, given relatively weak balance sheets among younger Americans before and after the Great Recession, and given that economically vulnerable families assumed greater balance sheet risk heading into the recession, efforts to build healthy, diversified balance sheets early in life should be strongly considered. Third, policies that establish savings accounts at birth or when entering kindergarten, which have been enacted or proposed at the local, state and national levels, hold particular promise and thus merit further consideration by policymakers, researchers, and others. Fourth, efforts to build savings and assets early in life are likely to yield benefits to children, families, and the economy. Further research and demonstration efforts are critical to moving this agenda forward.